2012
DOI: 10.1179/1743285511y.0000000025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mineralogy on reducibility of calcined nickel saprolite ore by hydrogen

Abstract: The aim of the work reported here was to examine the effect of mineralogy on reducibility of three different nickel saprolite ores originating from Brazil (Mirabela deposit) and from Colombia (Cerro Matoso S.A. deposit) as well as find the optimal reduction conditions for the ores. The reduction experiments were carried out in a thermobalance furnace at constant temperatures 600, 750 and 900uC in H 2 /N 2 (72%/28%) gas mixture, followed with scanning electron microscopy (SEM-EDS) and chemical analyses. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 16 publications
1
12
0
1
Order By: Relevance
“…Therefore, in the case of the Colombian ores, the reduction rate of removable oxygen at 750uC after a reduction time of 45 min was not as high as that of the Mirabela. For comparison, the CO reduction results, together with the results of reduction experiments for the same ores in an H 2 /N 2 (72% : 28%) atmosphere performed earlier by the present authors (Bunjaku et al, 2012), are shown in Figs. 5-7.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Therefore, in the case of the Colombian ores, the reduction rate of removable oxygen at 750uC after a reduction time of 45 min was not as high as that of the Mirabela. For comparison, the CO reduction results, together with the results of reduction experiments for the same ores in an H 2 /N 2 (72% : 28%) atmosphere performed earlier by the present authors (Bunjaku et al, 2012), are shown in Figs. 5-7.…”
Section: Resultsmentioning
confidence: 92%
“…More particularly, when saprolitic ore is reduced in a conditioned gaseous atmosphere, both nickel and iron are formed simultaneously by reduction and the resultant ferronickel has a comparatively low nickel content (Szekely and Evans, 1971;Bunjaku et al, 2012).…”
Section: Resultsmentioning
confidence: 98%
“…Nickel's economical, strategic and metallurgical importance has been thoroughly discussed in many works (Bolt 1967; Elias 2002; Halikia et al 2002; Zevgolis 2004; Mäkinen & Taskinen 2008; Mudd 2009; Rhamdhani et al 2009; Rhamdhani et al 2009; Bunjaku et al 2011; Kobayashi et al 2011; Bunjaku et al 2012; Bunjaku et al 2012; Swinbourne 2014). From cradle to grave, significant works measuring its technical competencies have been investigated by many researchers (Gleeson 2003; Guo 2009; Habashi 2009; Solar & Mostaghel 2015).…”
Section: Introductionmentioning
confidence: 99%
“…ser encontrados na literatura (Watanabe et al, 1987;Utigard et al, 2005;O'connor et al, 2006;Chang et al, 2008;Rhamdhani et al, 2009b;a;Zevgolis et al, 2010;Bunjaku et al, 2012;Samouhos et al, 2012;Li, Y.-J. et al, 2013;Rao et al, 2013;Pickles et al, 2014;Pickles e Elliott, 2015).…”
Section: Redução De Minérios Lateríticosmentioning
confidence: 99%
“…al (2012) estudaram a redução de três minérios saprolíticos de níquel utilizando gás hidrogênio como fase redutora e mostraram que a composição mineralógica desses minérios é um fator que influência diretamente na sua redutibilidade, os autores observaram que a presença de vermiculita em um minério brasileiro tornou o mesmo mais redutível, o que foi atribuído à formação de piroxênios que são minerais mais fáceis de serem reduzidos. No entanto, da quantidade total de ferro e níquel presente nesse mesmo minério, os melhores valores de redutibilidade obtidos foram de apenas 38%, o que é mais uma evidência da grande dificuldade em promover a redução do níquel dessa fração mineralógica do depósito laterítico (Bunjaku et al, 2012). Wang et al (2013) estudaram a redução de um minério laterítico com altos teores de silício (17%) e magnésio (17,4%) pelo carbono sólido e por CO(g).…”
Section: Redução De Minérios Lateríticosunclassified